Pengaruh Biaya Pemasaran Dan Gaji Karyawan Terhadap Laba Perusahaan Jasa Outsourcing Di PT. Aeon Delight Indonesia - Siregar, Marupa; Ernita Siagian; Lambas Marisi Tua LG (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
This research aims to determine the effect of marketing costs and salaries on company profits, both partially and simultaneously on capital structure. The research design used is quantitative descriptive. The population in this study were employees and consumers of PT. Aeon Delight Indonesia as many as 127 respondents. The sample in this study was 96 respondents. Data analysis used instrument tests, classical assumption tests, multiple linear regression statistical tests, hypothesis tests, correlation and determination tests. The research results show that marketing costs influence company profits, employee salaries influence company profits and company costs and employee salaries simultaneously influence company profits.